Optimalisasi Pola Tanam Berdasarkan Ketersediaan Air di Daerah Irigasi Oepunu Desa Billa Kecamatan Amanuban Timur - Creata, Maria Faustina Vini; Nasjono, Judi K; Hunggurami, Elia (JURNAL SUMBER DAYA AIR, 2025)
Water availability is a crucial factor that must be considered in the planning and management of irrigation systems. This study aims to determine water requirements based on a proposed rice–rice–secondary crops cropping pattern in the Oepunu Irrigation Area. This irrigation area encompasses 111 hectares of functional land and 20 hectares of potential land, with the current cropping pattern being rice–secondary crops. To ensure sufficient water supply, a study is necessary to design an effective cropping pattern. This research employed the Modified Penman method to calculate evapotranspiration, the F.J. Mock method to estimate dependable discharge, and direct streamflow measurements. The dependable discharge obtained ranges from 1,02 to 8,38 m³/s. The average discharge from direct measurements during the dry season (May-II to July-II) was 0,26 m³/s. The irrigation water requirements for the alternative cropping patterns are as follows: Alternative I ranges from 0,02–0,32 m³/s, Alternative II from 0,03–0,30 m³/s, and Alternative III from 0,03–0,24 m³/s. Based on the calculations, the maximum irrigable land area is 316.49 hectares for Alternative I, 274.95 hectares for Alternative II, and 948.87 hectares for Alternative III. These figures exceed the available land area, indicating that the selection of a cropping pattern must be based on the planned discharge derived from both irrigation water requirement calculations and field measurements. The planned discharge values are 0,32 m³/s for Alternative I, 0,30 m³/s for Alternative II, and 0,24 m³/s for Alternative III. Based on these planned discharge values, the most suitable cropping pattern is Alternative III, with a planned discharge of 0,24 m³/s and measured available discharge of 0,26 m³/s.